Comparison of Serenoa repens, lycopene, and selenium versus dutasteride for the treatment of LUTS/BPH: an Italian multicenter case-control prospective study (COMP study) - Morgia, Giuseppe; Lo Giudice, Arturo; Cimino, Sebastiano; Reale, Giulio; Larganà, Gaetano; La Manna, Enza; Madonia, Massimo; Tedde, Alessandro; Santaniello, Francesco; Vespasiani, Giuseppe; Zaganelli, Stefano; Arnone, Salvatore; et al. (Frontiers in Urology, 2025)
IntroductionHistorically, medical therapy of BPH has had its foundations in alpha-blockers in monotherapy or in combination with 5 alpha reductase inhibitors (5-ARIs); in particular, two important trials (COMBAT and MTOPS) have demonstrated the pivotal role of combination therapy instead of monotherapy and have individuated which patients are most likely to benefit from alpha-blockers, 5-ARIs, or their combination. However different side effects of these drugs, such erectile dysfunction, ejaculatory disorders, loss of libido, could affect the adherence to treatment. In fact, SeR-Se-Ly would work by blocking 5-alpha reductase and the binding between the dihydrotestosterone and the androgen receptor, antagonizing the a1-adrenergic receptor, and preventing cell proliferation and the production of COX-2 and 5-leukotrienes. Prior randomized controlled trials confirmed the use of alpha-blockers in conjunction with Lipidic Extract (LE) of Serenoa Repens (SeR), specifically compounds containing both Selenium (Se) and Lycopene (Ly). Based on these premises, the aim of this Italian multicenter case-control prospective non-randomized study is to compare the therapy with SeR-Se-Ly alone versus Dutasteride alone against BPH, in order to research a good therapeutic alternative with limited side effects.Materials and methodsFrom April 2021 to April 2022, 269 consecutive patients from 21 Italian centers were enrolled in this case-control study. The inclusion criteria were: age between 55 and 80 years old, digital rectal examination negative for prostate nodules, PSA<<4 ng/ml, IPSS<>12, prostate volume >40 cc (assessed by ultrasound), Qmax <<15 ml/sec. Patients with prostate cancer, prior bladder cancer, diabetes mellitus, neurogenic disorders, severe liver disease, history of orthostatic hypotension or syncope, recent a-blocker treatment (within 1 month) or phytotherapy, including saw palmetto extract (within 3 months), prior medical therapy with 5-ARI or surgical treatment for LUTS/BPH, patients with catheter or QoL, Qmax measured at an episode of acute urine retention within the last 4 weeks, and patients with any ejaculatory disorders were excluded. During treatment period, patients received SeR-Se-Ly for one year (Group A), or Dutasteride 0.5mg for one year (Group B). The main outcome measures included International Prostatic Symptoms Score (IPSS) and IPSS quality-of -life (QoL), International Index of Erectile Function (IIEF-5), Qmax measured at uroflowmetry and the Male Sexual Health Questionnaire (MSHQ).ResultsWe have observed increasing of Qmax of 2 points in group A and 2,5 points group B; IPSS has been reduced of 4 points in group A and 4,5 points in group B; IIEF-5 didn’t change in group A and it has been reduced in group B by -1; regarding the MSHQ, only the item MSHQ-Satisfaction has changed in group A: -1, in group B MSHQ was reduced by -2 points in ED, by -5 points in EJ, by -2,5 points in Satisfaction, by -0,5 points in Intercourse, by -3,2 points in Desire.ConclusionsSeR-Se-Ly could be a valid alternative to dutasteride, providing comparable effects on symptoms related to LUTS/BPH and avoiding sexual dysfunctions. SeR-Se-Ly should not be substituted for dutasteride in those patients for whom prostate volume reduction is desired.